Myrtus communis extract ameliorates high-fat diet induced brain damage and cognitive function - ŞEN, ALİ; ERTAŞ, BÜŞRA; ÖZBEYLİ, DİLEK; ŞENER, GÖKSEL (MARMARA UNIV, 2020)
Obesity causes cognitive weakening and increases the risk of neurodegenerative diseases. Myrtus connnunis extract (MC) has anti-inflammatory and antioxidant properties. In this study, it is aimed to investigate the effects of Myrtus comniunis on oxidative brain damage caused by a high-fat diet (HFD), using behavioral and biochemical parameters. Twenty- four Wistar albino rats (200-250 g) were divided into three groups. The control group (C) received a standard diet, while HFD groups were received HFD for 16 weeks. MC (100 mg/kg, oral) was given to the HFD + MC group for the last 4 weeks. At the end of the study, the novel object recognition test (NORT) was performed and the hippocampus and blood samples were collected. Acetylcholinesterase (AChE) and Na+/K+- ATPase activities, malondialdehyde (MDA), 8-hydroxy-2'-deoxyguanosine (8-0HdG) and reduced glutathione (GSH) levels were measured in the hippocampal samples and cholesterol levels were analyzed in sera. Findings have shown that NORT performance of the HFD group was reduced, while administration of MC prevents this reduction and in parallel, increased AChE and decreased Na+/K+-ATPase activities were ameliorated by administration of MC. Increased MDA and 8-OHdG levels observed in the HFD group, were decreased in the MC treated HFD group. Our results point out that MC has ameliorative effects on hippocampal oxidative stress and cognitive impairment in high fat nutrition-induced obesity.
Keywords: Obesity; oxidative stress; Myrtus communis; acetylcholinesterase; BODY-MASS INDEX; OXIDATIVE STRESS; ANTIOXIDANT DEFENSE; OBJECT RECOGNITION; ALZHEIMERS-DISEASE; DNA-DAMAGE; OBESITY; INJURY; INFLAMMATION; MECHANISMS